Management of allergic diseases in pregnancy. Issue 3 (4th September 2021) - Pfaller, Birgit; Bendien, Sarah; Ditisheim, Agnès; Eiwegger, Thomas
Abstract: Allergic diseases like asthma, allergic rhinitis, food allergy, hymenoptera allergy, or atopic dermatitis are highly prevalent in women of childbearing age and may affect up to 30% of this age group. This review focuses on the management of allergic diseases during pregnancy. Furthermore, we discuss the challenges of counseling women with allergic diseases in the reproductive age, including considerations relevant to the ongoing SARS‐CoV‐2 pandemic. To create the optimal milieu for the unborn child, a multitude of immunological changes occur during pregnancy which may favor type 2 responses and aggravate disease phenotypes. In co‐occurrence with suboptimal preconception disease control, this elevated Th2 responses may aggravate allergic disease manifestations during pregnancy and pose a risk for mother and child. Due to limitations in conducting clinical trials in pregnant women, safety data on anti‐allergic drugs during pregnancy are limited. The lack of information and concerns among pregnant patients demands counseling on the benefits of anti‐allergic drugs and the potential and known risks. This includes information on the risk for mother and child of disease aggravation in the absence of treatment. By doing so, informed decisions and shared decision‐making can take place.